Brain Rot as a Mediator of Social Media Use, Mental Well-Being, and Employee Productivity - Adi Muhammad Nur Ihsan; Sri Sudiarti; Arief Hamdan Syarief; Abdul Wildan; Abdul Hakim (Institut Teknologi dan Bisnis Asia Malang, 2026)
The rapid advancement of digital technology has intensified the use of social media in daily work activities, yet excessive information exposure may reduce individuals’ cognitive capacity. This study aims to analyze the mediating role of brain rot in the relationship between social media use, mental well-being, and employee productivity. A total of 282 active workers in Indonesia participated as respondents through a survey instrument adapted from previous studies, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that social media use and mental well-being have negative effects on brain rot, while brain rot negatively affects employee productivity. Furthermore, brain rot significantly mediates the relationship between social media use and productivity, as well as the relationship between mental well-being and productivity. These findings highlight that declining cognitive capacity serves as a crucial mechanism linking digital behavior and psychological conditions to work performance, offering empirical contributions to the literature on digital overstimulation and its implications in the workplace, while also providing opportunities for future research on interventions to minimize the negative effects of digital content consumption on productivity.